Protein kinase RNA‐like ER kinase/eukaryotic translation initiation factor 2α pathway attenuates tumor necrosis factor alpha‐induced apoptosis in nucleus pulposus cells by activating autophagy. Issue 7 (4th December 2018) - Chen, Lu; Liu, Lei; Xie, Zhi‐Yang; Wang, Feng; Zhu, Lei; Zhang, Cong; Fan, Pan; Sinkemani, Arjun; Hong, Xin; Wu, Xiao‐Tao
Abstract: Cellular loss induced by tumor necrosis factor alpha (TNF‐α) contributes to the pathogenesis of intervertebral disc (IVD) degeneration. Cellular stress induced by TNF‐α activates several processes to restore cell homeostasis. These processes include autophagy, endoplasmic reticulum stress, and related unfolded protein response (UPR). However, the effect and mechanism of UPR and autophagy regulated by TNF‐α in IVD degeneration (IDD) remain unclear. The effect of autophagy on biological changes in nucleus pulposus cells (NPCs) also remains elusive. In this study, rat NPCs were cultured with TNF‐α in the presence or absence of the UPR or autophagy pathway small‐interfering RNAs. The associated genes and proteins were evaluated through immunofluorescence staining, quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blot analyses to monitor UPR and autophagy signaling and identify the regulatory mechanism of autophagy by the UPR pathway. Trypan blue exclusion assay, cell flow cytometry, terminal deoxynucleotidyl transferase dUTP nick end labeling staining, qRT‐PCR, and western blot analyses were performed to examine the apoptosis of NPCs. The results showed that the acute exposure of TNF‐α induced the apoptosis of rat NPCs and activated the protein kinase RNA‐like ER kinase/eukaryotic translation initiation factor 2α (PERK/eIF2α) pathway of UPR and initiated autophagy. Silencing the PERK/eIF2α pathway or inhibiting autophagy enhanced the apoptosis of NPCs. Interference of the PERK/eIF2α pathway suppressed the autophagy of rat NPCs under TNF‐α stimulation. Taken together, the PERK/eIF2α pathway reinforces the survival of NPCs under TNF‐α stimulation by activating autophagy. Therefore, PERK/eIF2α‐dependent autophagy could be a novel biological therapeutic target for IDD. Abstract : Protein kinase RNA‐like ER kinase/eukaryotic translation initiation factor 2α (PERK/eIF2α)‐mediated unfolded protein response (UPR) signaling causes a prosurvival shift by activating autophagy in nucleus pulposus cells (NPCs).